Does Inflation Targeting Matter for Output Growth? Evidence from Industrial and Emerging Economies - Mollick, André Varella; Torres, René Cabral; Carneiro, Francisco G. (Washington, DC: World Bank, 2012)
This paper examines the effects of inflation targeting on industrial and emerging economies' output growth over the "globalization years" of 1986-2004. Controlling for trade openness and two indicators of financial globalization, the authors find systematic positive and significant effects of inflation targeting on real output growth. In dynamic models, the findings show strong output persistence in industrial economies, in which partial and full inflation targeting regimes have a positive long-run impact on growth. In emerging markets, only full inflation targeting policies have any output effect in the long-run. The results suggest that strict inflation targeting is needed to make the discipline effect of the disinflation process outweigh the output costs of promoting high interest rates to attract capital flows in a global world. These findings are robust to the treatment of endogenous globalization measures.